2016
DOI: 10.1089/chi.2015.0126
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Duration and Media Time Have a Major Impact on Insulin Resistance and Metabolic Risk Factors in Obese Children and Adolescents

Abstract: Short sleep duration was associated with IR and an elevated plasma lipoprotein profile in children and adolescents. Our results suggest that insufficient sleep and excessive media exposure may contribute to metabolic risk in the context of obesity, and therefore, working to improve sleep duration and limit media time could help reduce metabolic risk in obese children and adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
22
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 48 publications
3
22
0
Order By: Relevance
“…Moreover, poor sleep quality was the only lifestyle behavior associated with HOMA-IR. These findings are somewhat in agreement with previous studies that found an association between poor sleep quality/sleep deprivation and insulin resistance, especially among obese adolescents [35,36,37]. A possible mechanism underlying this association is related to an imbalance in autonomic modulation, given the fact that poor sleep quality may affect autonomic function through a decrease in parasympathetic modulation [38,39], and is also associated with impaired tissue response via insulin resistance [40].…”
Section: Discussionsupporting
confidence: 91%
“…Moreover, poor sleep quality was the only lifestyle behavior associated with HOMA-IR. These findings are somewhat in agreement with previous studies that found an association between poor sleep quality/sleep deprivation and insulin resistance, especially among obese adolescents [35,36,37]. A possible mechanism underlying this association is related to an imbalance in autonomic modulation, given the fact that poor sleep quality may affect autonomic function through a decrease in parasympathetic modulation [38,39], and is also associated with impaired tissue response via insulin resistance [40].…”
Section: Discussionsupporting
confidence: 91%
“…This association is consistent with the literature [25, 38, 39], and it is therefore important to propose setting limits on children’s exposure to screen-based forms of entertainment [40]. …”
Section: Discussionsupporting
confidence: 87%
“…Other pediatric studies indicate obese children and adolescents who report less than 9 h of sleep per night have higher fasting insulin and HOMA-IR levels, and lower high-density lipoprotein cholesterol (HDL-C) levels ( 42 ). Interestingly, a U-shaped distribution was observed, as those with intermediate sleep durations, 9–10 h for 10–13 year olds and 8–9 h for 14–15 year olds, had the lowest HOMA-IR, higher HDL-C, and lower aspartate aminotransferase (AST).…”
Section: Sleep Glucose Metabolism and Cardiometabolic Riskmentioning
confidence: 99%